2018
DOI: 10.1080/13880209.2018.1479869
|View full text |Cite
|
Sign up to set email alerts
|

Assessing product adulteration ofEurycoma longifolia(Tongkat Ali) herbal medicinal product using DNA barcoding and HPLC analysis

Abstract: Context: Eurycoma longifolia Jack (Simaroubaceae) commonly known as Tongkat Ali is one of the most important plants in Malaysia. The plant extracts (particularly roots) are widely used for the treatment of cough and fever besides having antimalarial, antidiabetic, anticancer and aphrodisiac activities. Objectives: This study assesses the extent of adulteration of E. longifolia herbal medicinal products (HMPs) using DNA barcoding validated by HPLC analysis. Materials and methods: Chloroplastic rbcL and nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Previous reports showed that a combination of DNA barcoding and HPLC successfully identified five Fritillariae bulbus species from TCM (Traditional Chinese Medicine) and its effective chemical constituents [49]. The authenticity of Eurycoma longifolia HMPs has been tested by DNA barcoding using the ITS2 marker, and its quality was verified using HPLC [50]. The quality of the famous Curcuma longa L. sold on the Chinese market was also assessed with DNA barcoding by discriminating the species using the ITS/LSU D1/D3 marker and HPLC to determine the chemical compositions [51].…”
Section: Hplc Fingerprinting Of L Pumila Hmpsmentioning
confidence: 99%
“…Previous reports showed that a combination of DNA barcoding and HPLC successfully identified five Fritillariae bulbus species from TCM (Traditional Chinese Medicine) and its effective chemical constituents [49]. The authenticity of Eurycoma longifolia HMPs has been tested by DNA barcoding using the ITS2 marker, and its quality was verified using HPLC [50]. The quality of the famous Curcuma longa L. sold on the Chinese market was also assessed with DNA barcoding by discriminating the species using the ITS/LSU D1/D3 marker and HPLC to determine the chemical compositions [51].…”
Section: Hplc Fingerprinting Of L Pumila Hmpsmentioning
confidence: 99%
“…Journal Homepage: https://eurekabiomedical.com/index.php/EHI antimalarials, antidiabetic, anticancer and aphrodisiac (Abubakar et al 2018). El can be consumed by combining its extracts in food or in drinks such as tea and coffee for the people of Malaysia (Ahmad et al 2018) and also the Batak ethnic group in Peadundung village is used as "tea" after activities in the fields (Silalahi and Nisyawati 2015).…”
Section: Eureka Herba Indonesiamentioning
confidence: 99%
“…Eurycoma distribution is limited in Southeast Asia(de Padua et al 1999), however some researchers claim it is also found in South Asia. E. longifolia and E Abubakar et al (2018). stated that DNA bar-coding with ITS2 barcodes can be used as the first screening step for HBP testing containing El.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of pharmacological activities of E. longifolia were antimicrobial, antidiabetic, cytotoxicity against cancerous cells, drug for sexual insuf iciency, immunomodulator, antiin lammation, etc. (Abubakar et al, 2018). In this article review, we aimed to examine the chemical substances and pharmacological activities of E. longifolia.…”
Section: Introductionmentioning
confidence: 99%